2020
DOI: 10.3389/fpsyg.2020.00442
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Contagious Yawning Is Highest Between Friends and Family Members: Support to the Emotional Bias Hypothesis

Abstract: Contagious yawning differs from spontaneous yawning because it occurs when an individual yawns in response to someone else's yawn. In Homo sapiens and some nonhuman primates contagious yawning is higher between strongly than weakly bonded individuals. Up to date, it is still unclear whether this social asymmetry underlies emotional contagion (a basic form of empathy preferentially involving familiar individuals) as predicted by the Emotional Bias Hypothesis (EBH) or is linked to a top-down, selective visual at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 69 publications
(90 reference statements)
6
38
0
Order By: Relevance
“…Inter-sexual biases in the power of eliciting a yawning response have been found in bonobos, where yawning in group mates can be induced most frequently by females 18 , and in humans (for vocalized yawns perceived only by hearing 31 ) and chimpanzees 30 where males as triggers are particularly effective in triggering others’ yawns. In humans, for vocalized yawns that are heard but not seen, it is possible that men’s vocalizations are better heard than women’s in natural settings, often characterized by background noises 31 . In chimpanzees and bonobos, the sex bias has been related to the dominance or social relevance of the triggering subjects, considering that in chimpanzees males are dominant 30 whereas in bonobos females acquire leadership by forming coalitions 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inter-sexual biases in the power of eliciting a yawning response have been found in bonobos, where yawning in group mates can be induced most frequently by females 18 , and in humans (for vocalized yawns perceived only by hearing 31 ) and chimpanzees 30 where males as triggers are particularly effective in triggering others’ yawns. In humans, for vocalized yawns that are heard but not seen, it is possible that men’s vocalizations are better heard than women’s in natural settings, often characterized by background noises 31 . In chimpanzees and bonobos, the sex bias has been related to the dominance or social relevance of the triggering subjects, considering that in chimpanzees males are dominant 30 whereas in bonobos females acquire leadership by forming coalitions 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans and great apes individual features can influence yawn contagion. These features include: (1) age (with the yawning response increasing from the immature period to adulthood; humans 28 ; chimpanzees 29 ; geladas 4 ); (2) sex of the trigger (females can elicit more yawns in bonobos 18 ; males can elicit more yawns in chimpanzees and in humans for yawns that are heard but not seen 30 , 31 ); (3) sex of the responder (with human females showing highest frequencies of response at least under certain conditions 32 ). Moreover, social factors, such as familiarity between trigger and responder, can also affect yawn contagion (humans 33 ; bonobos 18 , 34 ; chimpanzees 17 ; geladas 4 ; wolves 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, susceptibility to contagious yawning is positively related to performance on cognitive empathy measures, such as Theory of mind tasks, and negatively related to schizotypal traits (Platek et al, 2003). In addition, contagious yawning tends to be greatest in response to kin, then friends, then acquaintances, and lastly strangers (Norscia and Palagi, 2011;Norscia et al, 2020)a pattern consistent with other empathic behaviors (Preston andde-Waal, 2002, although Massen et al, 2015, reported that participants were no more likely to yawn contagiously to a member of their political "in" vs. "out" group). Furthermore, contagious yawning is not present in infants or toddlers (Helt et al, 2010) but rather develops during the preschool years (Cordoni et al, 2021) along the same timeline as other empathic abilities (Perner and Lang, 1999).…”
Section: Contagion and Empathymentioning
confidence: 99%